PENGARUH CITA RASA, PROMOSI, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MARTABAK FAVORIT DI UNGARAN - Febriana, Jesica; Supraptini, Nunuk; Ayu, Pitaloka Dharma (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
Favorite Martabak is a business in the culinary field which was founded in early 2019 which is located on Jl. RA Kartini 01, Sembungan, West Ungaran, Kab. Semarang. In running its business Martabak Favorit is still fluctuating the level of sales. The problems faced by Martabak Favorit include inconsistent tastes, promotions that have not been able to increase sales, price increases that occur and location. This type of research uses associative quantitative research. Data collection techniques through observation (observation) and questionnaires. The sampling technique in this study was carried out using a non-probability sampling method using a purposive sampling technique. Analysis of the data used is the analysis of correlation, regression, coefficient of determination, hypothesis testing with t test and f test. The partial test results show that the taste variable (X1) and the promotion variable (X2) have no effect on the purchase decision (Y). While the price variable (X3) and location variable (X4) influence the purchase decision (Y). The results of the study simultaneously obtained that the variable taste (X1), promotion (X2), price (X3) and location (X4) simultaneously had a significant effect on purchasing decisions (Y) Favorite Martabak in Ungaran.Keywords: Taste, Promotion, Price, Location and Purchase Decision